Characterization and densification of hot pressed ZrCN-ZrO2 ceramics; Science of Sintering; Vol. 57, iss. 4 - Kuzmenko E. D. Egor Dmitrievich; Matrenin S. V. Sergey Veniaminovich; Liang Yicheng; Voronova G. A. Gulnara Alfridovna (2025, 2025)
Title screen